Association of culprit lesion location with outcomes of culprit-lesion-only vs immediate multivessel percutaneous coronary intervention in cardiogenic shock: a post hoc analysis of a randomized clinical trial - Farhan, Serdar; Vogel, Birgit; Montalescot, Gilles; Barthelemy, Olivier; Zeymer, Uwe; Desch, Steffen; Waha-Thiele, Suzanne de; Maier, Lars S.; Sandri, Marcus; Akın, Ibrahim; Fuernau, Georg; Ouarrak, Taoufik; et al. (JAMA cardiology, 2020)
Myocardial infarction with a culprit lesion located in the left main or proximal left anterior descending artery compared with other coronary segments is associated with more myocardium at risk and worse clinical outcomes.To evaluate the association of culprit lesion location with outcomes of culprit-lesion-only percutaneous coronary intervention with optional staged revascularization vs immediate multivessel percutaneous coronary intervention in patients with multivessel disease, myocardial infarction, and cardiogenic shock.Post hoc analysis of the Culprit Lesion Only Coronary Intervention vs Multivessel Coronary Intervention in Cardiogenic Shock (CULPRIT-SHOCK), an investigator-initiated randomized, open-label clinical trial. Patients with multivessel disease, acute myocardial infarction, and cardiogenic shock were enrolled at 83 European centers from April 2013 through April 2017.Patients were randomized to culprit-lesion-only percutaneous coronary intervention with optional staged revascularization or immediate multivessel percutaneous coronary intervention (1:1). For this analysis, patients were stratified by culprit lesion location in the left main or proximal left anterior descending artery group and other-culprit-lesion location group.End points included a composite of death or kidney replacement therapy at 30 days and death at 1 year.The median age of the study population was 70 (interquartile range, 60-78 years) and 524 of the study participants were men (76.4%). Of the 685 patients, 33.4% constituted the left main or proximal left anterior descending artery group and 66.6% the other-culprit-lesion location group. The left main or proximal left anterior descending artery group had worse outcomes compared with the other-culprit-lesion location group (56.8% vs 47.5%; P = .02 for the composite end point at 30 days and 59.8% vs 50.1%; P = .02 for death at 1 year). In both groups, culprit-lesion-only vs immediate multivessel percutaneous coronary intervention was associated with a reduced risk of the composite end point at 30 days (49.1% vs 64.3% and 44.1% vs 50.9%; P for interaction = .27). At 1 year, culprit-lesion-only vs immediate multivessel percutaneous coronary intervention was associated with a significantly reduced risk of death in the left main or proximal left anterior descending artery but not the other-culprit-lesion location group (50.0% vs 69.6%; P = .003 and 49.8% vs 50.4%; P = .89; P for interaction = 0.02).In patients with multivessel disease with myocardial infarction and cardiogenic shock, a culprit lesion located in the left main or proximal left anterior descending artery vs other coronary segments was associated with worse outcomes. These patients may especially benefit from culprit-lesion-only percutaneous coronary intervention with optional staged revascularization, although further investigation is needed to confirm this finding.ClinicalTrials.gov Identifier: NCT01927549.